2006
DOI: 10.1152/ajpendo.00052.2005
|View full text |Cite
|
Sign up to set email alerts
|

Age-related loss of associations between acute exercise-induced IL-6 and oxidative stress

Abstract: mediates many aspects of the exercise-induced acute-phase response, including upregulation of antioxidant defenses. Moreover, IL-6 synthesis is regulated in part by oxidative stress. This investigation tested the hypothesis that an IL-6-mediated acute-phase response after exercise provides negative-feedback protection against exerciseinduced oxidative stress. Healthy young (n ϭ 16, 26.4 Ϯ 1.8 yr) and older men (n ϭ 16, 71.1 Ϯ 2.0 yr) ran downhill for 45 min at 75% maximal oxygen consumption before and after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
0
33
2
4
Order By: Relevance
“…In contrast with the findings of the studies described above (26, 27, 153), another exercise study reported no differences in neutrophil counts or plasma IL-6 concentration between young (18 -35 yr) and elderly men (65-80 yr) after 45 min downhill running (130). The reasons for this disparity are unclear but may include differences between these exercise studies (26, 27, 130, 153) regarding the intensity and mode of exercise, the age, and habitual physical activity of the study participants.…”
Section: Aging Muscle Injury and Inflammationcontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast with the findings of the studies described above (26, 27, 153), another exercise study reported no differences in neutrophil counts or plasma IL-6 concentration between young (18 -35 yr) and elderly men (65-80 yr) after 45 min downhill running (130). The reasons for this disparity are unclear but may include differences between these exercise studies (26, 27, 130, 153) regarding the intensity and mode of exercise, the age, and habitual physical activity of the study participants.…”
Section: Aging Muscle Injury and Inflammationcontrasting
confidence: 71%
“…The reasons for this disparity are unclear but may include differences between these exercise studies (26, 27, 130, 153) regarding the intensity and mode of exercise, the age, and habitual physical activity of the study participants. The plasma concentrations of IL-1ra, sTNF-␣R1, TGF-␤, and Creactive protein increased similarly after exercise in both young and elderly men (130,153). These findings suggest that not all systemic inflammatory reactions to exercise-induced muscle injury change with age.…”
Section: Aging Muscle Injury and Inflammationmentioning
confidence: 78%
“…Estudos examinando o efeito de breves sessões de exercícios máximos (< 10 min) não encontraram alterações agudas nas concentrações séricas de IL-6 26 , entretanto, aumentos nos níveis circulantes desta citocina foram identi cados após 15 minutos 27 , 60 minutos 28 , e seis horas 29 de recuperação.…”
Section: Discussionunclassified
“…In fact, it was demonstrated that the circulating cytokine levels increase with age and there is some evidence that ageing is associated with a remarkable cytokine response following stimulation, although these eVects are presently well-known only for elderly populations (Krabbe et al 2004). However, no studies have shown until now a positive relationship between contraction-related IL-6 production and age: Sacheck et al (2006) have recently found that the magnitude of post-exercise changes in acute phase variables is independent of age.…”
Section: Discussionmentioning
confidence: 99%